2009
DOI: 10.1017/s0007114509993023
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometric, metabolic, psychosocial and dietary factors associated with dropout in overweight and obese postmenopausal women engaged in a 6-month weight loss programme: a MONET study

Abstract: The objective of the present study was to examine anthropometric, metabolic, psychosocial and dietary factors associated with dropout in a 6-month weight loss intervention aimed at reducing body weight by 10 %. The study sample included 137 sedentary, overweight and obese postmenopausal women, participating in a weight loss intervention that consisted of either energy restriction (ER) or ER with resistance training (ER+RT). Anthropometric (BMI, percent lean body mass, percent fat mass, visceral adipose tissue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 43 publications
(80 reference statements)
3
21
0
Order By: Relevance
“…Despite the higher drop-out rate (57% at 6 months) observed in our study, our findings are generally in line with those reported in recent studies with a similar treatment duration [5,17,31]. Our results indicate that few baseline variables (%BF, diastolic blood pressure, type of referral, and age at first dieting attempt) significantly differed between completers and noncompleters.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Despite the higher drop-out rate (57% at 6 months) observed in our study, our findings are generally in line with those reported in recent studies with a similar treatment duration [5,17,31]. Our results indicate that few baseline variables (%BF, diastolic blood pressure, type of referral, and age at first dieting attempt) significantly differed between completers and noncompleters.…”
Section: Discussionsupporting
confidence: 90%
“…High drop-out rates from obesity treatment have been associated with baseline characteristics such as young age [3,9-11], low education levels [6,9,12], poor dieting behaviors [3,5,8,12,13], and unhealthy lifestyles [12-15]. However, the literature on predictors of attrition in obesity treatment is limited by different study designs and inconsistencies across studies.…”
Section: Introductionmentioning
confidence: 99%
“…Several researchers have previously demonstrated that initial weight loss is associated with study dropout in dietary based weight loss trials [9][10][11][12][13][14][15][16] , however this finding is not consistent and others have found no relationship 11,17,18 . This is the first study to quantify the amount of initial weight loss which predicts dropout and to investigate and quantify additional easily obtainable subject characteristics such as age which can be used to ensure adequate randomisation.…”
Section: Discussionmentioning
confidence: 99%
“…Where a relationship does exist it appears that females may be more likely to drop out than males 2 , although a more recent study has shown that males are more likely to drop out than females 23 . The 2011 systematic review found roughly equal (but small n=4-5) numbers of papers supporting a relationship between high or low initial weight and attrition compared with 18 reporting no relationship more recent papers continue to differ with some supporting the relationship between higher initial weight 18,20 and attrition and some lower initial weight 15 (although no relationship is still the most frequent 9,17,19 ).…”
Section: Discussionmentioning
confidence: 99%
“…10.1 percent of the participants terminated the program after the fi rst group session. Th is percentage appears low in comparison to other weight loss programs [9,17,21]. Drop-out is detected to be one of the causes of success in weight reduction.…”
Section: Drop-outmentioning
confidence: 93%